Tata Laksana SAR Minor untuk Mengurangi Rekurensi dan Keparahan - Endah Ayu Tri Wulandari; Titiek Setyawati (Faculty of Dentistry, Universitas Indonesia, 2013)
Recurrent aphthous stomatitis (RAS) is an inflammatory condition of oral mucosa and is very common that occur in 20% of population, in which 80% of all cases are minor type. Etiology remains unknown but there are factors that can precipitate the attack, known as predisposing factors, which are haematinic deficiency, food hypersensitivity, bacterial or viral infection, hormonal changes, psychological stress, drugs and local trauma. Management of minor RAS are symptomatic and also discovering all predisposing factors which may play role in order to give the appropriate treatments to all predisposing factors. The appropriate treatment for all predisposing factors is to prevent recurrency or reduce the severity of RAS.This paper presents 2 cases of minor RAS which have bacterial infection from poor oral hygiene; local trauma from radices, irritating tooth cusp and rough surface of calculus; haematinic deficiency; physical / psychological stress and food hypersensitivity, as predisposing factors. The management of those cases are scaling, grinding irritating cusp, giving advice of proper and healthy diet including vitamin supplementation, finding any stress factor and also overcome it. We concluded that finding and eliminating predisposing factors can reduce recurrency and severity of RAS. DOI: 10.14693/jdi.v15i2.72